Real-Time Hardware-in-the-Loop Tests of Star Tracker Algorithms - Giancarlo Rufino; Domenico Accardo; Michele Grassi; Giancarmine Fasano; Alfredo Renga; Urbano Tancredi (International Journal of Aerospace Engineering)
This paper deals with star tracker algorithms validation based on star field scene simulation and hardware-in-the-loop test configuration. A laboratory facility for indoor tests, based on the simulation of star field scenes, is presented. Attainable performance is analyzed theoretically for both static and dynamic simulations. Also, a test campaign is presented, in which a star sensor prototype with real-time, fully autonomous capability is exploited. Results that assess star field scene simulation performance and show the achievable validation for the sensor algorithms and performance in different operating modes (autonomous attitude acquisition, attitude tracking, and angular rate-only) and different aspects (coverage, reliability, and measurement performance) are discussed.